2011
DOI: 10.1088/0967-3334/32/12/006
|View full text |Cite
|
Sign up to set email alerts
|

Indirect measurement of lung density and air volume from electrical impedance tomography (EIT) data

Abstract: This paper describes a method for estimating lung density, air volume and changes in fluid content from a non-invasive measurement of the electrical resistivity of the lungs. Resistivity in Ω m was found by fitting measured electrical impedance tomography (EIT) data to a finite difference model of the thorax. Lung density was determined by comparing the resistivity of the lungs, measured at a relatively high frequency, with values predicted from a published model of lung structure. Lung air volume can then be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
4
16
0
1
Order By: Relevance
“…derived by Ref. 57 and similarly observed in several experiments (45,47,48). We used a mean tortuosity of ϭ 1.71, an alveolar conductivity of alv ϭ 0.7284 ⍀/cm and the volumetric strain was converted to the filling factor FF ϭ V air/Vtissue via FF ϭ 5.0•εvol -5.0, which came from the assumption that the filling factor was FF ϭ 3.0 at functional residual capacity (FRC) and FF ϭ 6.0 at total lung capacity (TLC) (57).…”
Section: And Is Described In Appendix Asupporting
confidence: 82%
“…derived by Ref. 57 and similarly observed in several experiments (45,47,48). We used a mean tortuosity of ϭ 1.71, an alveolar conductivity of alv ϭ 0.7284 ⍀/cm and the volumetric strain was converted to the filling factor FF ϭ V air/Vtissue via FF ϭ 5.0•εvol -5.0, which came from the assumption that the filling factor was FF ϭ 3.0 at functional residual capacity (FRC) and FF ϭ 6.0 at total lung capacity (TLC) (57).…”
Section: And Is Described In Appendix Asupporting
confidence: 82%
“…Results for the resistivity dependence on the filling factor in our model and in literature. Nopp, 1993[36] Nopp 1997, ρ(FRC)=10Ω m Nebuya, 2011[35] Wang, 2014 ventilation, even though they do not match exactly. This can be explained by the neglect of surrounding soft tissues, which clearly has an influence on the image reconstruction (Adler and Lionheart 2006).…”
Section: Nonlinearity Of the Tortuositymentioning
confidence: 99%
“…It has been demonstrated that an increase in lung volume from the residual volume to the vital capacity volume can result in an increase in electrical resistance by more than double [20]. Electrical impedance tomography provides information about thoracic resistance on each section and thereby, degree of their aeration.…”
Section: Physical Principles Of Electrical Impedance Tomographymentioning
confidence: 99%